2013
DOI: 10.1136/vr.101377
|View full text |Cite
|
Sign up to set email alerts
|

Schmallenberg virus: a seroprevalence survey in cattle and sheep, France, winter 2011–2012

Abstract: In France, a national surveillance plan to monitor congenital Schmallenberg virus (SBV) outbreaks was set up in January 2012, and has shown that SBV had become widespread throughout the country since mid-2011. However, the number of SBV-infected farms cannot accurately be estimated through congenital SBV reporting alone. Therefore, GDS France (National Animal Health Farmers' Organization) conducted serological investigations in cattle and sheep holdings in several departments in spring 2012 to assess SBV expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 1 publication
1
23
1
Order By: Relevance
“…No significant difference in seroprevalence was found between case and control flocks. This is in line with a serosurvey on SBV in sheep in France [5]. Because of the relatively low number of flocks that submitted sufficient samples for a reliable within-flock seroprevalence estimation, it was decided to estimate within-flock seroprevalence based on flocks that submitted 50 or more samples.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…No significant difference in seroprevalence was found between case and control flocks. This is in line with a serosurvey on SBV in sheep in France [5]. Because of the relatively low number of flocks that submitted sufficient samples for a reliable within-flock seroprevalence estimation, it was decided to estimate within-flock seroprevalence based on flocks that submitted 50 or more samples.…”
Section: Discussionmentioning
confidence: 81%
“…Between clinically affected and not-clinically affected flocks no significant differences in seroprevalences were found [5]. A seroprevalence of 89.0% was found in sheep samples sampled between November 2011 and March 2012 in the Netherlands [6].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Additionally, there is a single report of SBV-specific antibodies in a dog, but other studies have failed to find evidence of infection in carnivores (Wensman and others 2013, Mouchantat and others 2015). European studies, conducted in 2011, 2012 and 2013, found animal-level prevalence to range between 8 to 100 per cent and 8.5 to 93.3 per cent in cattle and sheep, respectively (Elbers and others 2012, Gache and others 2013, Nanjiani and others 2013). Herd-level prevalence of UK sheep in 2012/2013 was found to range between 40 and 90 per cent (Nanjiani and others 2013).…”
mentioning
confidence: 99%
“…This has been shown even in areas where prevalence is high and so it does not follow that flock positivity always conforms (Gache and others 2013). Vaccine may not always suppress viraemia, but it will offer protection in these circumstances and will lessen the likelihood of recrudescence of disease at repeated intervals.…”
Section: Where Next?mentioning
confidence: 99%